British Muslims Caught Amidst FOGs—A Discourse Analysis of Religious Advice and Authority - Usman Maravia; Zhazira Bekzhanova; Mansur Ali; Rakan Alibri (Religions, 2021)
This paper discusses the symbolic capital found within Islamic documents that were circulated in the UK during the COVID-19 outbreak. Specifically, the work explores “fatwas” and “other” similar documents as well as “guidance” documents (referred to as FOGs) that were disseminated in March–April 2020 on the internet and social media platforms for British Muslim consumption. We confine our materials to FOGs produced only in English. Our study takes its cue from the notion that the existence of a variety of documents created a sense of foggy ambiguity for British Muslims in matters of religious practice. From a linguistic angle, the study seeks to identify (a) the underlying reasons behind the titling of the documents; and (b) the construction of discourses in the documents. Our corpus-assisted critical discourse analysis (CA-CDA) found noticeable patterns that hold symbolic capital in the fatwa register. We also found that producers of “other” documents imitate the fatwa register in an attempt to strengthen the symbolic capital of their documents. Accordingly, fatwas act as the most authoritative documents in religious matters and are written by senior religious representatives of the Muslim community, whereas guidance documents were found to be most authoritative in health matters. The findings raise questions regarding the manner in which religious instruction may be disseminated in emergency situations. Based on this study, a call for the standardisation and unification of these diverse and sometimes contradicting religious publications may be worth considering.